Sustainability of Digital Payments in Economic Development: A Systematic Literature Review on Technology Acceptance Model - Lestari Rezki Nurul Amalia; Grace Theresia Pontoh; Syarifuddin Rasyid; Muhammad Irdam Ferdiansah (Penerbit Goodwood, 2026)
Purpose: This study aims to understand the factors influencing the continued use of digital payments in economically developing countries. It applies the Technology Acceptance Model (TAM) and integrates other relevant variables that support long-term adoption and promote economic development. Methodology/approach: This study used a systematic literature review of 35 research papers published between 2020 and 2024. The studies were collected from different academic databases and reviewed using the PRISMA protocol. Results/Findings: The main TAM factors (such as perceived usefulness and ease of use) strongly affect people’s intention to continue using digital payments, explaining 41.3% of the behavior. When combined with other factors, such as trust, service quality, motivation, and social support, the prediction increased to 61%. These additional factors are important, especially when considering different social and economic situations. Conclusions: An extended TAM model is useful for understanding why people continue to use digital payments. It can support sustainable economic growth and help more people gain access to financial services. Limitations: This study only considered papers published from 2020 to 2024; therefore, it may not include all relevant research published outside this period. Contributions: This study contributes to the literature on digital finance, economic development, and technology acceptance. It offers insights for researchers, policymakers, and financial service providers to develop more adaptive and user-centered digital payment systems.